Caries prevalence and treatment needs of 7- to 10-year-old schoolchildren in southwestern Germany - Zerfowski, Martin; Koch, Martin Jean; Niekusch, Uwe; Staehle, Hans Jörg (Community dentistry and oral epidemiology, 1997)
The caries status of 1784 children aged 7 to 10 years was examined in a cross-sectional, epidemiological study in the Rhine-Neckar-District. Results showed that 30.5% of the children had caries-free primary and 65.2% had caries-free permanent teeth. The d(m)ft index was 2.68, and the D(M)FT averaged 0.76. As in previous studies, a high risk caries group was found, with 10% of all children showing more than 50% of all carious and filled teeth in the permanent dentition. Overall, 45.6% of the children's primary teeth and 16.3% of their permanent teeth needed treatment. As indicated by higher DT:F T (DT:FT) ratios in younger age groups, dentists preferred treating older children. Apart from a higher caries prevalence in primary teeth in males, no significant sex differences were found. Children of rural origin had a higher caries experience. The results confirm previous data showing considerable improvements with a declining caries experience in the young population. But the caries status of German pre-teenage children is still moderately high according to WHO criteria. For further improvements, considerable efforts have to be made with special emphasis on prevention in high risk caries groups.